Standardized ketamine infusion protocol for chronic refractory pain: a retrospective study of preliminary effectiveness and treatment completion - Tankha, Hallie; Davin, Sara; Lapin, Brittany; Li, Yadi; Kennemer, Austin; Schuster, Andrew; Xu, Jijun; Gopalakrishnan, Raghavan; Tankha, Pavan (Regional anesthesia and pain medicine, 2025)
Chronic refractory pain presents limited treatment options and diminished quality of life. While ketamine treatment shows promise, protocol variations and safety concerns have hindered widespread adoption. This study evaluated preliminary effectiveness and rate of treatment completion for a standardized low-dose ketamine infusion therapy (KIT) protocol. This retrospective observational study examined adult patients with chronic refractory pain who received KIT between May 2021 and October 2024 at the Cleveland Clinic's outpatient multidisciplinary pain clinic. Patients received a standardized protocol of 0.5 mg/kg ketamine infused over 40 min for five consecutive days. We measured effectiveness using patient-reported outcomes (PROs) at baseline, last infusion, and 3-month and 6-month post-treatment, and rate of treatment completion. The primary outcome of interest was the proportion of patients achieving clinically meaningful improvement on validated measures. Among 1034 patients (mean age 50.4±15.2 years; 71.8% female; 83.3% of white ethnicity), treatment completion was high, with 890 (86.1%) patients completing 5+ infusions. No adverse events were reported. Baseline measures reflected moderate impairment in pain interference, global physical health, fatigue, physical function, and depression. Between 20.3% and 46.4% of patients achieved clinically meaningful improvement on PROs from baseline to last infusion, with similar proportions maintained at 3-month and 6-month follow-up. Statistically significant mean improvements were observed across multiple domains; however, the majority of individual outcomes did not reach clinically meaningful thresholds. Patients demonstrated significant mean improvements in fatigue, pain interference, and social role satisfaction (mean change -2.1±7.7, -2.0±5.8, and 2.0±7.7, respectively), with improvements in depression, social role satisfaction, pain interference, self-efficacy, global health, and pain catastrophizing sustained through 6 months post-treatment. This standardized low-dose ketamine protocol demonstrated therapeutic benefit and high completion rates within a multidisciplinary care model. Future randomized controlled trials are warranted to confirm findings and explore treatment response factors across pain conditions.